(untitled) (Contemporary Journal of Social Science Review, 2025)
Objective: This study applies Immanuel Kant’s aesthetic theory to analyze the poem Seasons of Heart by a Pakistani poet named Farzana Aqib (Aqib, 2023, p. 106), focusing on how readers experience beauty through emotion, meaning, and admiration. Method: A qualitative approach was used with thematic analysis to explore Kant’s three concepts including the agreeable (personal feelings), the good (moral meaning), and the beautiful (pure admiration) within the poem. Findings: The poem connects with readers emotionally, encourages personal growth, and offers artistic beauty. The analysis shows that Kant’s theory helps us understand poetry on emotional, ethical, and aesthetic levels.